2020
DOI: 10.1177/1176934320939943
|View full text |Cite
|
Sign up to set email alerts
|

Family-Specific Gains and Losses of Protein Domains in the Legume and Grass Plant Families

Abstract: Protein domains can be regarded as sections of protein sequences capable of folding independently and performing specific functions. In addition to amino-acid level changes, protein sequences can also evolve through domain shuffling events such as domain insertion, deletion, or duplication. The evolution of protein domains can be studied by tracking domain changes in a selected set of species with known phylogenetic relationships. Here, we conduct such an analysis by defining domains as “features” or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 205 publications
0
3
0
Order By: Relevance
“…Co‐IP and immunofluorescence assays further confirmed our hypothesis that ENKUR binds to MYH9. In the tertiary structure of a protein, domain is considered as an independent folding unit and has different functions 36,37 . After constructing plasmids with different domains, we found that Enkurin was the key domain for ENKUR in playing an antimetastatic role and interacting with MYH9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co‐IP and immunofluorescence assays further confirmed our hypothesis that ENKUR binds to MYH9. In the tertiary structure of a protein, domain is considered as an independent folding unit and has different functions 36,37 . After constructing plasmids with different domains, we found that Enkurin was the key domain for ENKUR in playing an antimetastatic role and interacting with MYH9.…”
Section: Discussionmentioning
confidence: 99%
“…In the tertiary structure of a protein, domain is considered as an independent folding unit and has different functions. 36,37 After constructing plasmids with different domains, we found that Enkurin was the key domain for ENKUR in playing an antimetastatic role and interacting with MYH9. In addition, the Myosin tail domain was also found to be the element interacting with ENKUR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Zf-met structural domain was found in the amino acid sequence of HVA22 in the three species of wild tomatoes. The Zf-met domain is another zinc-finger domain containing the CxxC(12)Hx(6)H motif, which is associated with RNA binding ( Yadav, Fernández-Baca & Cannon, 2020 ). This is similar to the structure identified in the tomato HVA22 protein.…”
Section: Discussionmentioning
confidence: 99%